Host transcriptomic signatures of tuberculosis can predict immune reconstitution inflammatory syndrome in HIV patients. Issue 7 (27th April 2022) - Mbandi, Stanley Kimbung; Painter, Hannah; Penn‐Nicholson, Adam; Toefy, Asma; Erasmus, Mzwandile; Hanekom, Willem A.; Scriba, Thomas J.; Lai, Rachel P.J.; Marais, Suzaan; Fletcher, Helen A.; Meintjes, Graeme; Wilkinson, Robert J.; et al.
Abstract: Immune reconstitution inflammatory syndrome (IRIS) can be a complication of antiretroviral therapy (ART) in patients with advanced HIV, but its pathogenesis is uncertain. In tuberculosis (TB) endemic countries, IRIS is often associated with mycobacterial infections or Bacille‐Calmette‐Guerin (BCG) vaccination in children. With no predictive or confirmatory tests at present, IRIS remains a diagnosis of exclusion. We tested whether RISK6 and Sweeney3, validated immune‐based blood transcriptomic signatures for TB, could predict or diagnose IRIS in HIV+ children and adults. Transcripts were measured by RT‐qPCR in BCG‐vaccinated children and by microarray in HIV+ adults with TB including TB meningitis (TBM). Signature scores before ART initiation and up to IRIS diagnosis were compared between participants who did or did not develop IRIS. In children, RISK6 and Sweeney3 discriminated IRIS cases from non‐IRIS controls before ART, and at diagnosis. In adults with TB, RISK6 discriminated IRIS cases from controls after half‐week on ART and at TB‐IRIS onset. In adults with TBM, only Sweeney3 discriminated IRIS cases from controls before ART, while both signatures distinguished cases from controls at TB‐IRIS onset. Parsimonious whole blood transcriptomic signatures for TB showed potential to predict and diagnose IRIS in HIV+ children and adults. Abstract : Host blood‐derived biomarkers based on tuberculosis parsimonious transcriptomic signatures showed potential to predict and diagnose immune reconstitution inflammatory syndrome upon initiation of antiretroviral therapy in children and adults with HIV.